The Role Of The Reprimand Speech Act As A Tool For Attention And Influence In Context - Ataboyev Isroiljon Mirza o‘g‘li (Open Academia, 2025)
This article analyzes the role of the reprimand speech act in context and its functional capacity in communicative processes. A reprimand is not only a tool for correcting behavior but also a means of reinforcing social norms, restoring moral values, and regulating interpersonal communication. The study explores the effectiveness, attention-drawing potential, and contextual dependence of reprimands based on the four functions identified by N.A.Karaziya regulative, cathartic, manipulative, and phatic. The article also explains the cultural variability and social significance of reprimands from both linguistic and pragmalinguistic perspectives.
Keywords: Reprimand speech; context